Collateral pial circulation relates to the degree of brain edema on CT 24 hours after ischemic stroke. Issue 5 (October 2018) - Galego, Orlando; Jesus-Ribeiro, Joana; Baptista, Mariana; Sargento-Freitas, João; Martins, Ana Inês; Silva, Fernando; Santos, Gustavo Cordeiro; Cunha, Luís; Nunes, César; Machado, Egídio
Background: Cerebral edema is frequent in patients with acute ischemic stroke (AIS) who undergo reperfusion therapy and is associated with high mortality. The impact of collateral pial circulation (CPC) status on the development of edema has not yet been determined. Methods: We studied consecutive patients with AIS and documented M1–middle cerebral artery (MCA) and/or distal internal carotid artery (ICA) occlusion who underwent reperfusion treatment. Edema was graded on the 24-hour non-contrast computed tomography (NCCT) scan. CPC was evaluated at the acute phase (≤6 hours) by transcranial color-coded Doppler, angiography and/or CT angiography. We performed an ordinal regression model for the effect of CPC on cerebral edema, adjusting for age, baseline National Institutes of Health Stroke Scale, Alberta Stroke Program Early Computed Tomography Score (ASPECTS) on admission, NCCT, parenchymal hemorrhagic transformation at 24 hours and complete recanalization at six hours. Results: Among the 108 patients included, 49.1% were male and mean age was 74.2 ± 11.6 years. Multivariable analysis showed a significant association between cerebral edema and CPC status (OR 0.22, 95% CI 0.08–0.59, p  = 0.003), initial ASPECTS (OR 0.72, 95% CI 0.57–0.92, p  = 0.007) and parenchymal hemorrhagic transformation (OR 23.67, 95% CI 4.56–122.8, p  < 0.001). Conclusions: Poor CPC is independently associated with greater cerebral edema 24 hours after AIS in patients who undergo reperfusion treatment.